Storage dynamics simulations in prairie wetland hydrology models: evaluation and parameterization. Issue 13 (28th May 2013) - Shook, Kevin; Pomeroy, John W.; Spence, Christopher; Boychuk, Lyle
Abstract: The contributing areas of streams in the Prairie regions of Canada and the northern U.S. are dominated by complexes of wetlands which store and release water. Prior research has suggested the existence of hysteresis between the total volume of water stored in prairie wetlands within a drainage basin and the basin's contributing area. To simulate the relationship between storage and contributing area in a way that accounts for hysteresis, two wetland hydrology models with vastly different levels of complexity were devised. The fully distributed Wetland Digital Elevation Model (DEM) Ponding Model (WDPM) applies simple fluxes of runoff and evaporation to a DEM of a prairie wetland complex. The parameterized Pothole Cascade Model (PCM) applies simulated fluxes of water to collections of conceptual models of wetlands and is less demanding in computations and data. Prior research showed that both models produced hysteretic relationships between water storage and contributing area, but the PCM produced smaller estimates of contributing area than did the WDPM, likely due to its spatial simplification. Using sequential remote sensing observations of wetland area after snowmelt, this study shows that the frequency distribution of the open water areas of prairie wetlands is similar to that produced by the WDPM when the wetlands are close to being completely filled. The remotely sensed observations show evidence of hysteresis in the open water area frequency distributions, as predicted by the fully distributed WDPM. To enable the parameterized PCM to produce the same type of hysteretic relationships as the WDPM, scaling relationships between the maximum area of a wetland and the area of upland draining into it were included. The parameterized PCM is suitable for application with prairie snow redistribution, snowmelt, infiltration, runoff and evapotranspiration routines as part of semi‐distributed hydrological modelling of prairie wetland basins such as that implemented in the Cold Regions Hydrological Model. Copyright © 2013 John Wiley & Sons, Ltd.